Efficacy of surgical treatment of patients with symptomatic cystocele - Mekan R. Orazov; Vyacheslav N. Lokshin; Yulia I. Ruzimatova; Anastasia E. Pavlova (Клинический разбор в общей медицине, 2024)
Pelvic organ prolapse is a problem with no ideal solution. Unfortunately, there is still no unified opinion about etiopathogenesis of genital prolapses in general and cystocele in particular. The aim of the study is to increase the effectiveness of surgical treatment in patients with symptomatic cystocele, by double plication of the pubocervical fascia. Materials and methods. The study included 112 patients with symptomatic cystocele of grade II–IV according to POP-Q system, who underwent different variants of surgical treatment method: I – comparison group (n=60) – traditional anterior colporrhaphy; II – the main group (n=52) by the method of double plication of pubocervical fascia. The average age of the patients of the studied cohort was 53.2±9.6 years. The duration of follow-up after surgical treatment was 12 months. The frequency of intra- and postoperative complications, as well as anatomical (recurrence rate) and functional (levelling of cystocele symptoms) treatment results were evaluated. Study. Patients in the study cohort did not differ in age, anthropometric data, social status and clinical characteristics of the underlying disease (p≥0.05). Analysis of early postoperative complications, as well as anatomical and functional results of treatment demonstrated statistically significant advantages of surgical correction of cystocele by double plication of the pubocervical fascia, compared to traditional anterior colporrhaphy (p<0.05). Conclusions. Double pleating of the pubocervical fascia appears to be an effective and safe surgical technique for the treatment of patients with symptomatic cystocele: it significantly (p<0.05) improves anatomical and functional outcomes of treatment and 2.5 times reduces the recurrence rate during 12 months of follow-up, compared to traditional anterior colporrhaphy.